History as Aesthetics in the African Novel: a Reading of Kane’s Ambiguous Adventure - Afolayan, Sola (EAST WEST JOURNAL OF HUMANITIES, 2012)
Introduction: VOL 3, 2012 Sola Afolayan University of Ado Ekiti African literature is as unique as the African people themselves. This is because, among other reasons, there is no way it can be interpreted outside the people and their past experiences. This is why it seems as if every African novel is a piece of history. Hyppolyte Taine, the father of historical determinism in literary criticism, has postulated that the best critical outfit which can evaluate the works of literature will first consider the history that is behind the author of the work, stressing that: It was perceived that a work of literature is not a mere play of imagination, a solitary caprice of a heated brain, but a transcript of contemporary manners, a type of a certain kind of mind. It was concluded that one might retrace from the moment of literature the style of man’s feelings and thought for centuries back (1971:602)